2015
DOI: 10.1002/ptr.5447
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in preclinical drug–drug interaction studies of flavonoids — Review of case studies, issues and perspectives

Abstract: Because of health benefits that are manifested across various disease areas, the consumption of herbal products and/or health supplements containing different kinds of flavonoids has been on the rise. While the drug-drug interaction potential between flavonoids and co-ingested drugs still remain an issue, opportunities exist for the combination of flavonoids with suitable anti-cancer drugs to enhance the bioavailability of anti-cancer drugs and thereby reduce the dose size of the anti-cancer drugs and improve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 77 publications
(154 reference statements)
0
30
1
Order By: Relevance
“…These include patients with impaired kidney function and with estrogen‐dependent cancer, because quercetin may aggravate kidney failure and may promote tumor formation in these patients, respectively (Andres et al, ). Quercetin and some of its metabolites may produce pharmacokinetic interactions with several drugs, primarily due to modulation of biotransformation enzymes and drug transporters (Miron et al, ; Srinivas, ). It has been reported that quercetin inhibits CYP enzymes (CYP3A4 and CYP2C9), sulfotransferases (SULT1), organic anion transporters (OAT1), organic anion‐transporting polypeptides (OATP1A2 and OATP2B1), and ATP‐binding cassette transporters (MRP1, P‐gp, and BCRP); while it increases the expression of CYP3A4, CYP1A1, and P‐gp (Kimura et al, ; Miron et al, ; Poór et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…These include patients with impaired kidney function and with estrogen‐dependent cancer, because quercetin may aggravate kidney failure and may promote tumor formation in these patients, respectively (Andres et al, ). Quercetin and some of its metabolites may produce pharmacokinetic interactions with several drugs, primarily due to modulation of biotransformation enzymes and drug transporters (Miron et al, ; Srinivas, ). It has been reported that quercetin inhibits CYP enzymes (CYP3A4 and CYP2C9), sulfotransferases (SULT1), organic anion transporters (OAT1), organic anion‐transporting polypeptides (OATP1A2 and OATP2B1), and ATP‐binding cassette transporters (MRP1, P‐gp, and BCRP); while it increases the expression of CYP3A4, CYP1A1, and P‐gp (Kimura et al, ; Miron et al, ; Poór et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Because flavonoids and many prescribed medications share phase I and II metabolic processes, the effects of dietary flavonoid (and other bioactive) intake on drug ADME and dosing amounts have been of research and clinical interest for several decades (8689). The impact of grapefruit consumption on cytochrome-3A4 activity and the metabolism of a large number of drug groups, such as calcium channel antagonists β-hydroxy-β-methylglutaryl–CoA reductase inhibitors and antihistamines, represents a widely cited example (90, 91).…”
Section: Etiology Of the Heterogeneity In Flavonoid Admementioning
confidence: 99%
“…For example, hesperidin has been shown to undergo extensive phase 2 conjugation, involving both glucuronosyltransferases and sulfotransferases in in vitro systems; similarly, biacalin and biochanin A demonstrate remarkable phase 2 metabolism. Overall, biliary mechanisms tend to be important for the disposition of flavonoids, as well as determining the drug-drug interaction potential with coadministered drugs [3,4].…”
Section: ó Springer International Publishing Switzerland 2015mentioning
confidence: 99%